PLANNING AND DECISION MAKING IN THE CONTESTATION OF NEW SANTRI RECRUITMENT AT PESANTREN MIFTAHUL ULUM RENES WIROWONGSO AJUNG JEMBER - Halid, Ahmad (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2023)
This article discusses the planning and decision -making of kiai dakam new student admission contest covering a study on decision -making models, decision -making processes and determining the purpose of decision making. Job satisfaction and increased creativity, personal development and acceptance of change depend on decision -making by an organization. A good manager or leader is a manager and leader who is based on the exchange of ideas and cooperation rather than based on authority and arrogance in his position. This research is a qualitative approach and descriptive analysis. Using data collection methods: observation, interviews and documentation. This is done by the kiai in the pesantren to give a decision based on an exchange of opinions and then taken the most positive impact and then delegated to his subordinates to work together to develop the organization. The kiai policy-making process is done in consultation and the pesantren work team is given the authority to carry out their respective duties. So that the recruitment process of new students runs smoothly and increasing every year